(untitled) (Minerva, 2019)
The sexual behaviour that the Greek ancient novel displays as a model is personified by a heterosexual couple. They are both young and very attractive, and belong to the highest social class. This relationship is based, specially in the case of the young female, on complete self-control due to the influence of stoicism. Their objective is a happy and stable married life. The influence of certain mysteric religions and the approval of the authorities is clearly visible in the construction of this model.